2012
DOI: 10.1259/bjr/91904659
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dual-source and electron-beam CT for the assessment of coronary artery calcium scoring

Abstract: Objective: Cardiac CT allows the detection and quantification of coronary artery calcification (CAC). Electron-beam CT (EBCT) has been widely replaced by high-end CT generations in the assessment of CAC. The aim of this study was to compare the CAC scores derived from an EBCT with those from a dual-source CT (DSCT). Methods: We retrospectively selected 92 patients (61 males; mean age, 60.7¡12 years) from our database, who underwent both EBCT and DSCT. CAC was assessed using the Agatston score by two independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The CT scans were repeated with the same system and protocol, so that we avoided the use of any correction factors, which otherwise would have been needed using different types of scanners. 14 , 25 , 32 A 5-year follow-up period may be too short, but may allow an extrapolation to longer time intervals based on the exponential percentile curvature, which remained constant over time. In addition, we found for some patient, for whom we had during a 10-year follow-up multiple CT scans, that their individual CAC progression followed the age- and gender-related exponential curvature calculated form our baseline data of the total cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The CT scans were repeated with the same system and protocol, so that we avoided the use of any correction factors, which otherwise would have been needed using different types of scanners. 14 , 25 , 32 A 5-year follow-up period may be too short, but may allow an extrapolation to longer time intervals based on the exponential percentile curvature, which remained constant over time. In addition, we found for some patient, for whom we had during a 10-year follow-up multiple CT scans, that their individual CAC progression followed the age- and gender-related exponential curvature calculated form our baseline data of the total cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium scores might be underestimated by MDCT, 26 and particularly in obese patients. 27 However, other studies have shown that CAC scores are comparable between EBCT and MDCT [28][29][30][31] and for that matter the MESA calculator combined the CAC scores derived with both types of scanners. 32 Finally, we had to exclude 3 studies, the MESA, the study by Hopkins et al and the study by Park et al, 9,12,13 since they used 10-year age strata instead of 5-year strata as we did.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Finally, prospective trials which measure CAC and delineate the consequences in primary prophylaxis are needed. In the study, the CAC score was measured by the use of different CT-scanners (EBCT versus MSCT), but these two techniques are considered as equal in measuring the CAC score [28,29].…”
Section: Limitationsmentioning
confidence: 99%